Land use and land conversion in Iloilo Province - Dagoon, Jinky L.
This paper investigates the land use pattern and land conversion issues in the province of Iloilo. Using four sets of data from the Department of Agrarian Reform, Department of Agriculture, and the Department of Environment and Natural Resources, the study reveals that, during the period covered by the study (1981-2000), the patterns of land utilization in the province of Iloilo showed minor changes, with the bulk of land are still devoted mainly to agriculture. There was a concious effort on the part of landowners to convert their lands to non-agricultural uses. The government countered this effort by drawing a set of strick guidelines to prevent unnecessary conversions. The findings of this study suggest that, the authorities were able to limit, to some extent, the conversion of lands from agricultural to urban use. However, peasant organizations view government policies on land conversion as ineffective in elevating the socioeconomic status of small farmers. The present study views land conversion issues in the light of market failure in land markets and the role of government in choosing between competing uses of land.